Intervening factors experienced by the refugee population in the reception of the public health service: integrative review (Research, Society and Development, 2023)
The objective of this study was to analyze the intervening factors experienced by the refugee population in the reception offered by the public health service. This is an integrative literature review, in which an electronic search was carried out on the CAPES Portal de Periódicos, crossing the descriptors: Refugees, Right to Health and Health Care. After the searches, 2,611 texts were found, which after reading them in full, 18 were selected for the final sample. It was possible to demonstrate the barriers experienced in health centers, including lack of information about health systems, difficulty in communicating and understanding the language, cultural differences, legal and protection issues, in addition to lack of financial resources. Priority was given to this field of investigation, due to the fact that there are difficulties and gaps in knowledge about access to health for refugees, as well as the challenges for adherence to measures capable of guaranteeing qualified assistance.